CEA Level, Radical Surgery, CD56 and CgA Expression Are Prognostic Factors for Patients With Locoregional Gastrin-Independent GNET. Issue 18 (May 2016) - Li, Yuan; Bi, Xinyu; Zhao, Jianjun; Huang, Zhen; Zhou, Jianguo; Li, Zhiyu; Zhang, Yefan; Li, Muxing; Chen, Xiao; Hu, Xuhui; Chi, Yihebali; Zhao, Dongbing; et al.
Abstract : Abstract: Gastrin-independent gastric neuroendocrine tumors (GNETs) are highly malignant. Radical resections and lymphadenectomy are considered to be the only possible curative treatment for these tumors. However, the prognosis of gastrin-independent GNETs is not well defined. In this study, we identified prognostic factors of locoregional gastrin-independent GNETs. All patients diagnosed with locoregional gastrin-independent GNETs between 2000 and 2014 were included in this retrospective study. Clinical characteristics, blood tests, pathological characteristics, treatments, and follow-up data of the patients were collected and analyzed. Of the 66 patients diagnosed with locoregional gastrin-independent GNETs, 57 (86.4%) received radical resections, 7 (10.6%) with palliative resection, 1 (1.5%) with gastrojejunostomy, and 1 (1.5%) with exploration surgeries. The median survival time for these patients was 19.0 months (interquartile range, 11.0–38.0). The 1-, 3-, and 5-year survival rates were 72%, 34%, and 28%, respectively. Multivariate analysis indicated that carcinoembryonic antigen (CEA) level ( P = 0.04), radical resection ( P = 0.04), and positive Cluster of Differentiation 56 (CD56) expression ( P = 0.016) were significant prognostic factors on overall survival rate. Further univariate and multivariate analysis of 57 patients who received radical resections found that CgA expression ( P = 0.35) and CEA level ( P = 0.33) are independent prognostic factors. Gastrin-independent GNETs had poor prognosis. Serum CEA level, radical surgery, CD56 and CgA expression are markers to evaluate the survival of patients with locoregional gastrin-independent GNETs.